Finance and welfare states in globalizing markets - Giuseppe Bertola (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
It is theoretically clear and may be verified empirically that efficient financial markets can make it less necessary for policy to try and offset the welfare effects of labour income risk and unequal consumption dynamics. The literature has also pointed out that, since international competition exposes workers to new sources of risk at the same time as it makes it easier for individual choices to undermine collective policies, international economic integration makes insurance-oriented government policies more beneficial as well as more difficult to implement. This paper reviews the economic mechanisms underlying these insights and assesses their empirical relevance in cross-country panel data sets. Interactions between indicators of international economic integration, of government economic involvement, and of financial development are consistent with the idea that financial market development can substitute public schemes when economic integration calls for more effective household consumption smoothing. The paper's theoretical perspective and empirical evidence suggest that to the extent that governments can foster financial market development by appropriate regulation and supervision, they should do so more urgently at times of intense and increasing internationalization of economic relationships.
urn:nbn:de:hebis:30-51025
Keywords: G1; E21; 330; Finance; Welfare State; Globalization; Globalisierung; Internationaler Finanzmarkt; Lohn; Arbeitslosigkeit; Risiko; Steuersenkung; Einkommensverteilung; Welt